(untitled) (Olhar de Professor, 2023)
This theoretical essay seeks to focus on theoretical productions, documents and studies that can contribute to the understanding of the concept of polycentric accessibility and its potential in the Brazilian educational context. The purpose of this essay is to provide education professionals with a greater field of research and, mainly, ways to reframe their educational and management practices in relation to the schooling of all, including people with disabilities, global developmental disorders or high skills/giftedness.